PENGEMBANGAN VIDEO PEMBELAJARAN ANIMASI MENGGUNAKAN APLIKASI RENDERFOREST PADA MATERI SIKAPKU TERHADAP KEBERAGAMAN BUDAYA - Aina Mutmaina; Yuli Mulyawati; Aip M. Irpan (STKIP Subang, 2025)
This study employed a Research and Development (R&D) approach using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques involved observation, interviews, instrument sheets in the form of questionnaires for student and teacher responses, as well as pre-test and post-test questions. The aim of this study was to explore the development process of an animated learning video using the Renderforest application on the topic My Attitude Toward Cultural Diversity and to evaluate its feasibility and effectiveness in supporting the learning process.The research subjects consisted of four expert validators, one Grade IV teacher, and 23 Grade IV students of SDN Wanaherang 02. The product developed in this study is an animated learning video created using Renderforest, which was validated by media experts, language experts, and subject matter experts. Its feasibility was assessed through student response questionnaires, while its effectiveness was measured using pre-test and post-test results.The research findings indicate that the feasibility test results were: media expert 94%, language expert 100%, subject matter expert (lecturer) 96%, and subject matter expert (teacher) 98%. In addition, a limited trial involving 23 Grade IV students showed that the product received a very feasible rating with a score of 98%. The effectiveness test also demonstrated improvement, with pre-test results of 64.7% and post-test results of 92.1%. It can be concluded that the animated learning video developed using the Renderforest application is highly feasible and effective for use in the learning process.